INTERPRETASI SEJARAH LOKAL DAN PENGEMBANGAN JALUR WISATA DIGITAL BERBASIS QR CODE DI KAMPUNG KAUMAN YOGYAKARTA UNTUK SOLO TRAVELER - Makhasi, Ghifari Yuristiadhi Masyhari; Fakhrurrifqi, Muhammad (Universitas Negeri Malang, 2020)
Kauman kampong is a religious servant residence of Yogyakarta Sultanate which was formed along with the establishment of the Yogyakarta Sultanate Great Mosque in 1773. Muhammadiyah was founded in this kampong in 1912 which provided its own historical dynamics for this kampong. Since 2010 in Kauman kampong, Yogyakarta, the historical tour package